Development of innovative technology for sauce with lecithin - Kolesnichenko, Svetlana; Salavelis, Alla; Pavlovsky, Sergey; Poplavska, Svitlana (Technology audit and production reserves, 2021)
Consumers of catering establishments especially value their health and therefore give preference to dishes that correspond to modern concepts of healthy eating. In this regard, the development of such dishes is an important task. Thus, the object of the study was an emulsion sauce made using the spherification technique. Agar-agar was used as a material for encapsulating the sauce. The recipe composition of the sauce contains irreplaceable nutritional components: plant phospholipids (soy lecithin), monounsaturated and polyunsaturated fatty acids of olive oil and camelina oil, natural food fibers of agar-agar. Each recipe component of the developed emulsion sauce contains physiologically active substances with a high efficiency of health-improving effect. Synergy The combination of the positive effects of these prescription components makes it possible to create a therapeutic and prophylactic product. One of the most problematic areas is the formation of a lecithin-oil-water composition with a lamellar structure. Such a structure as a multilayer «container» helps to preserve the biologically active substances that make up the sauce from destruction and to better assimilate them by the human body. Due to the choice of a certain number of recipe components and their sequential combination under certain conditions (temperature 45 °C, mixing), it is possible to obtain a lamellar structure. In the course of the study, recipe components were selected that correspond to healthy food products, recipes and technologies for the preparation of an emulsion sauce with a lamellar structure were developed. And also provided with the help of spherification an attractive appearance and determined the organoleptic, microbiological indicators and shelf life of the product. To confirm the presence of the lamellar structure of the sauce, carry out optical studies and presented a micrograph in polarizing light. The research carried out makes it possible to expand the range of sauces with an extended shelf life (three days) for the restaurant industry.